2018
DOI: 10.1007/s10995-018-2500-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Inequities in Low Birth Weight and Preterm Birth: The Role of Multiple Forms of Stress

Abstract: Introduction Racial/ethnic inequities in low birth weight (LBW) and preterm birth (PTB) persist in the United States. Research has identified numerous risk factors for adverse birth outcomes; however, they do not fully explain the occurrence of, or inequalities in PTB/LBW. Stress has been proposed as one explanation for differences in LBW and PTB by race/ethnicity. Methods Using the Pregnancy Risk Assessment Monitoring System (PRAMS) data from 2012 to 2013 for 21 states and one city (n = 15,915) we used Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Our study provides rich, contextual description and measurement of racial disparities in perinatal health in the US beyond most previous population-based studies. First, our findings agree with other US-based studies finding wide disparities in birth outcomes by race and SEP (Almeida et al, 2018; Amjad et al, 2019; Blumenshine et al, 2010; Braveman et al, 2015; Culhane & Goldenberg, 2011; Grobman et al, 2018). Second, we uncover maternal LE patterns preceding US births that systematically disadvantage low-income and minority women, through differential clustering of toxic stressors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study provides rich, contextual description and measurement of racial disparities in perinatal health in the US beyond most previous population-based studies. First, our findings agree with other US-based studies finding wide disparities in birth outcomes by race and SEP (Almeida et al, 2018; Amjad et al, 2019; Blumenshine et al, 2010; Braveman et al, 2015; Culhane & Goldenberg, 2011; Grobman et al, 2018). Second, we uncover maternal LE patterns preceding US births that systematically disadvantage low-income and minority women, through differential clustering of toxic stressors.…”
Section: Discussionsupporting
confidence: 92%
“…But race still has residual effects on birth outcomes beyond what is explicable by SEP indicators, risky health behaviors ( e.g. , smoking or drinking), and healthcare access (Almeida, Becares, Erbetta, Bettegowda, & Ahluwalia, 2018; Lorch & Enlow, 2016; Lu & Chen, 2004). Furthermore, the improvements in birth outcomes with higher SEP among African Americans are not as pronounced as among whites (Braveman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is corroborated by other studies that have found racial and/or ethnic disparities in adverse labor outcomes and PPH morbidity in particular. 7 Racial disparities in perinatal health in general are multifactorial and may be related to differences in access to or engagement in care, 36 disparate hospital care practices, 37,38 racism and segregation, 39,40 pervasive stress, [41][42][43] or epigenetic effects. [44][45][46] Race and ethnicity are not included as part of published PPH risk scoring tools.…”
Section: Discussionmentioning
confidence: 99%